Step-by-step cross-linked high-toughness anion exchange membrane and preparation method thereof

Through step-by-step crosslinking method, the toughness and chemical stability of the anion exchange membrane are improved, and the problem of easy folding and perforation of anion exchange membrane in the prior art is solved, and anion exchange membrane with high toughness and high ion conductivity is realized. It is suitable for liquids Flow battery and fuel cell.

CN119161616APending Publication Date: 2024-12-20SUQIAN TIMES ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291362.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-30
Filing Date
2024-09-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing anion exchange membranes are not tough enough, and they are prone to crease and perforation due to external forces, resulting in low yield of flow batteries.

Method used

采用分步交联方法,首先在含部分苯乙烯结构的季胺化聚芳基哌啶型阴离子交换树脂溶液中进行第一步交联,然后加入硫醇试剂和光引发剂,在UV光照环境下进一步交联,形成高韧性阴离子交换膜。

Benefits of technology

It improves the toughness and chemical stability of the anion exchange membrane, enhances the ion conductivity, and is suitable for the fields of flow batteries and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161616A_ABST
    Figure CN119161616A_ABST
Patent Text Reader

Abstract

According to the step-by-step cross-linked high-toughness anion exchange membrane for the liquid flow energy storage battery and the preparation method of the step-by-step cross-linked high-toughness anion exchange membrane, a quaternized polyaryl piperidine anion exchange resin solution containing a part of styrene structure is subjected to one-step cross-linking under the action of an initiator; then adding a thiol reagent and a photoinitiator into the anion exchange resin solution cross-linked in the first step, coating, and initiating second-step cross-linking through UV illumination, so as to obtain the anion exchange resin. The step-by-step crosslinking anion exchange membrane disclosed by the invention is fully and orderly crosslinked, high in toughness and high in ionic conductivity, and has excellent electrochemical performance when being used for a liquid flow energy storage battery. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anion exchange membranes of liquid flow batteries, and in particular relates to a step-by-step cross-linked high-toughness anion exchange membrane and a preparation method thereof. Background Art

[0002] As a new electrochemical energy storage method, flow batteries can store discontinuous, unstable and uncontrollable wind power and photovoltaic power generation on demand and transform them into controllable and stable energy. It plays an important role in accelerating the establishment of a sound green, low-carbon and circular development economic system in China.

[0003] Anion exchange membrane is the core component of flow battery. At present, the mainstream structure with good chemical stability and high ion conductivity is polyaryl piperidine, such as Versogen TM PiperION TM Anion exchange membrane series. Since the anion exchange membrane of this structure is a rigid main chain, its toughness is very poor. In the actual application process of transporting and assembling flow batteries, it is very easy to be creased and perforated due to external forces, resulting in a low yield of flow batteries. Therefore, in the actual application process, it is very important to improve the toughness of the anion exchange membrane. Summary of the invention

[0004] In order to solve the above problems, the present invention discloses a step-by-step cross-linked high-toughness anion exchange membrane and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing a step-by-step cross-linked high-toughness anion exchange membrane, comprising the following steps:

[0007] An initiator is added to a solution of a quaternary ammonium polyaryl piperidine anion exchange resin containing a partial styrene structure, and the solution is heated in an oven to perform the first step of crosslinking. Then, a thiol reagent and a photoinitiator are added to the solution of the first step of crosslinking. After coating, the solution is placed under UV light for further crosslinking to form a film, that is, a high-toughness anion exchange membrane can be crosslinked step by step.

[0008] The tough anion exchange membrane has a structure shown in formula (1):

[0009]

[0010] Wherein, Ar1 and Ar2 can be independently selected from one or more of benzene, biphenyl, o-terphenyl, p-terphenyl, m-terphenyl, quaterphenyl, o-quaterphenyl, m-quaterphenyl, p-quaterphenyl, diphenylmethane and 1,2-diphenylethane;

[0011] The preparation method specifically comprises the following steps:

[0012] (1) dissolving a biphenyl monomer in a solvent, adding N-methyl-4-piperidone monomer, and continuously adding trifluoromethanesulfonic acid and trifluoroacetic acid under stirring in an ice bath at 0° C., pouring the obtained polymer into an alkaline solution and stirring after the reaction is completed, then washing with deionized water until neutral, and drying to obtain a polyaryl piperidine polymer;

[0013] (2) dissolving the polyaryl piperidine polymer obtained in step (1) in a solvent, adding iodomethane and 4-vinyl benzyl chloride, stirring at 35° C. in the dark, and completing the reaction. The mixture is poured into a cleaning solvent for cleaning, and the precipitate is washed with deionized water. An ion exchange is performed in a sodium chloride solution to obtain a quaternized polyaryl piperidine anion exchange resin containing a part of a styrene structure.

[0014] (3) dissolving the quaternized polyaryl piperidine type anion exchange resin containing a partial styrene structure prepared in step (2) in a solvent, adding an initiator, and heating in an oven to perform the first step of crosslinking to obtain a first step crosslinked anion exchange resin solution;

[0015] (4) Adding a thiol reagent and a photoinitiator to the first cross-linked anion exchange resin solution prepared in step (3), placing it under UV light for further cross-linking after coating, to obtain a step-by-step cross-linked high-toughness anion exchange membrane.

[0016] Furthermore, the biphenyl monomer is m-terphenyl or p-terphenyl, the molar ratio of m-terphenyl to p-terphenyl is 1:1-3, the molar ratio of N-methyl-4-piperidone monomer to m-terphenyl or p-terphenyl is 1:0.5-1, the volume ratio of trifluoromethanesulfonic acid to trifluoroacetic acid is 10:1-3, the volume ratio of the solvent to the total volume of trifluoromethanesulfonic acid and trifluoroacetic acid is 1:1.5-2, and the volume ratio of the solvent to the N-methyl-4-piperidone monomer is 4:1-1.5.

[0017] Furthermore, in step (1), the solvent is one of dichloromethane, chloroform, tetrachloroethane, and carbon tetrachloride, and the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, and potassium carbonate solution.

[0018] Furthermore, in step (2), the molar ratio of the polyaryl piperidine polymer, methyl iodide and 4-vinyl benzyl chloride is 1:1:0.15; the mass ratio of the polyaryl piperidine polymer to the solvent is 1:5-10; the solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide; and the cleaning solvent is one of ethanol, acetone, ethyl acetate and acetonitrile.

[0019] Furthermore, in step (3), the mass ratio of the quaternized polyaryl piperidine type anion exchange resin containing a portion of styrene structure to the initiator is 125:0.6-1; the mass ratio of the quaternized polyaryl piperidine type anion exchange resin containing a portion of styrene structure to the solvent is 1:5-10.

[0020] Furthermore, in step (3), the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, isomethyl azobisisobutyrate, and azobisisopropylimidazoline hydrochloride; the solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone, and N,N-dimethylformamide; and the temperature of the first cross-linking step is 80° C. and the time is 1 hour.

[0021] Furthermore, in step (4), the mass ratio of the thiol reagent, the photoinitiator and the first step cross-linking solution is 2:1:100-350; the conditions for further cross-linking are heating at 40-60°C and UV irradiation for 25 minutes.

[0022] Furthermore, in step (4), the thiol reagent is one or more of 1,10-decanethiol, 1,5-pentanethiol, 1,8-octanedithiol, 1,6-hexanethiol, and 3,6-dioxa-1,8-octanedithiol; and the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone.

[0023] The present invention also provides a step-wise cross-linked high-toughness anion exchange membrane prepared by the preparation method as described above, wherein the thickness of the step-wise cross-linked high-toughness anion exchange membrane is 30-80 μm.

[0024] The present invention also provides the application of the step-wise cross-linked high-toughness anion exchange membrane in a liquid flow battery.

[0025] The beneficial effects of the present invention are:

[0026] The step-wise cross-linked high-toughness anion exchange membrane prepared according to the present invention is obtained by cross-linking a rigid quaternized polyaryl piperidine polymer cast membrane. The membrane has the advantages of being fully cross-linked in order, high toughness, high chemical stability, high ionic conductivity, etc., and can be widely used in the field of liquid flow batteries and fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The dissolution of one-step cross-linked anion exchange membrane in dimethyl sulfoxide;

[0028] Figure 2 The figure shows the dissolution of the step-wise cross-linked anion exchange membrane of the present invention in dimethyl sulfoxide. DETAILED DESCRIPTION

[0029] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0030] Example 1

[0031] (1) Synthesis of polymer main chain: 2.3 g of p-terphenyl, 2.3 g of m-terphenyl and 3.1 g of N-methyl-4-piperidone were added to a 250 ml round-bottom flask in an ice bath, and then 10 ml of dichloromethane was added and stirred at 60 rpm. Then, 15 ml of trifluoromethanesulfonic acid and 1 ml of trifluoroacetic acid were added dropwise, and the stirring rate was increased to 230 rpm. The mixture was reacted at 0° C. for 36 h to obtain a viscous solution. The viscous solution was poured into deionized water for washing and filtration to obtain a light yellow solid. The light yellow solid was washed in a sodium hydroxide solution with a pH of 9 for 4-8 h, and then washed with deionized water until neutral, filtered and dried in an oven at 80° C. under vacuum for 48 hours to obtain a polymer product.

[0032] (2) Quaternization of the polymer main chain: 6.5 g of the polymer synthesized in (1) above was dissolved in 65 g of dimethyl sulfoxide and heated at 35° C. Then, 2.84 g of iodomethane, 0.52 g of 4-vinylbenzyl chloride and 2.76 g of potassium carbonate were added. The reaction was carried out in the dark for 48 h. The reaction solution was poured into ethyl acetate to precipitate a white solid. The solid was washed three times with deionized water and dried at 60° C. for 36 h to obtain a quaternized polyarylpiperidine anion exchange resin containing a partial styrene structure.

[0033] (3) First step crosslinking: 0.5 g of the quaternary ammonium polyaryl piperidine anion exchange resin containing a partial styrene structure obtained in (2) above was dissolved in 5 g of dimethyl sulfoxide, 4 mg of azobisisobutyronitrile was added, and then placed in an oven at 80° C. for 1 hour to obtain the first step crosslinking anion exchange resin solution.

[0034] (4) Second step cross-linking: take 5 g of the first step cross-linking anion exchange resin membrane liquid in the above (3), add 0.03 g of 3,6-dioxa-1,8-octanedithiol and 0.015 g of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and then coat it on a PET substrate. Heat it at 50° C. and irradiate it with UV light for 25 min to obtain a high-toughness anion exchange membrane that is cross-linked step by step.

[0035] Example 2

[0036] Take 5 g of the first step cross-linked anion exchange resin solution described in (3) of Example 1, add 0.06 g of 3,6-dioxa-1,8-octanedithiol and 0.03 g of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and then coat it on a PET substrate. Heat it at 50° C. and irradiate it with UV light for 25 min to obtain a high-toughness anion exchange membrane that is cross-linked step by step.

[0037] Example 3

[0038] Take 5 g of the first step cross-linked anion exchange resin solution described in (3) of Example 1, add 0.09 g of 3,6-dioxa-1,8-octanedithiol and 0.045 g of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and then coat it on a PET substrate. Heat it at 50° C. and irradiate it with UV light for 25 min to obtain a high-toughness anion exchange membrane that is cross-linked step by step.

[0039] Comparative Example 1

[0040] 5 g of the first step cross-linked anion exchange resin solution described in (3) of Example 1 was taken and directly coated, and then heated on a baking plate at 80° C. for 70 min to obtain a one-step cross-linked anion exchange membrane.

[0041] Comparative Example 2

[0042] 0.5 g of the quaternized polyaryl piperidine anion exchange resin containing a partial styrene structure obtained in (2) of the above Example 1 was dissolved in 5 g of dimethyl sulfoxide, and then 0.06 g of 3,6-dioxa-1,8-octanedithiol and 0.03 g of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone were added, and the mixture was heated at 50° C. and irradiated with UV light for 25 min to obtain a one-step cross-linked anion exchange membrane.

[0043] The step-wise cross-linked high-toughness anion exchange membrane prepared in the above-mentioned Examples 1-3 and the one-step cross-linked anion exchange membrane prepared in Comparative Example 1-2 were assembled as electrolyte membranes in an aqueous organic flow battery. The positive electrode active material of the electrolyte was TEMPO-ammonium chloride, the negative electrode active material of the electrolyte was 1,1-dimethyl-4,4'-bipyridinium dichloride, and the supporting electrolyte was sodium chloride. The above-mentioned assembled battery was subjected to charge and discharge cycle tests at 10-25°C, and the current density was 108 mA / cm 2

[0044] The performance comparison table of the cross-linked anion exchange membranes prepared in Examples 1-3 and Comparative Examples 1-2 is shown in Table 1 below. The tensile strength and elongation at break were obtained by testing according to the national standard GB / T 1040-92 method. The battery efficiency is the test result of a single cell of an organic flow battery.

[0045] Table 1 Comparison of the performance of anion exchange membranes prepared in Examples 1-3 and Comparative Examples 1-2

[0046]

[0047] As can be seen from Table 1, the step-by-step cross-linked high-toughness anion exchange membrane disclosed in the embodiment of the present invention has a very excellent elongation at break compared with the one-step cross-linked anion exchange membrane. This is due to the fact that the step-by-step cross-linking can obtain a fully cross-linked and orderly anion exchange membrane. As shown in the dissolution test shown in the figure below, the one-step cross-linked anion exchange membrane will break when dissolved in dimethyl sulfoxide, indicating that the membrane is a discontinuous cross-linked phase, while the step-by-step cross-linked high-toughness anion exchange membrane is still a complete membrane when dissolved in dimethyl sulfoxide, and the aqueous organic liquid flow battery assembled with the step-by-step cross-linked high-toughness anion exchange membrane material of the present invention shows good battery performance.

[0048] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a step-by-step cross-linked high-toughness anion exchange membrane, characterized in that: The tough anion exchange membrane is prepared by firstly performing a one-step crosslinking of a polyarylpiperidine anion exchange resin solution containing a part of the styrene structure quaternized under the action of an initiator, then adding a thiol reagent and a photoinitiator to the anion exchange resin solution of the first step crosslinking, and then initiating a second step crosslinking by UV light after coating; The tough anion exchange membrane has a structure shown in formula (1): Formula (1); Wherein, Ar1 and Ar2 can be independently selected from one or more of benzene, biphenyl, o-terphenyl, p-terphenyl, m-terphenyl, quaterphenyl, o-quaterphenyl, m-quaterphenyl, p-quaterphenyl, diphenylmethane and 1,2-diphenylethane.

2. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 1, characterized in that: The specific steps include: (1) dissolving a biphenyl monomer in a solvent, adding N-methyl-4-piperidone monomer, and continuously adding trifluoromethanesulfonic acid and trifluoroacetic acid under stirring in an ice bath at 0° C., pouring the obtained polymer into an alkaline solution and stirring after the reaction is completed, then washing with deionized water until neutral, and drying to obtain a polyaryl piperidine polymer; (2) dissolving the polyaryl piperidine polymer obtained in step (1) in a solvent, adding iodomethane and 4-vinyl benzyl chloride, stirring at 35° C. in the dark, and completing the reaction. The mixture is poured into a cleaning solvent for cleaning, and the precipitate is washed with deionized water. An ion exchange is performed in a sodium chloride solution to obtain a quaternized polyaryl piperidine anion exchange resin containing a part of a styrene structure. (3) dissolving the quaternized polyaryl piperidine type anion exchange resin containing a partial styrene structure prepared in step (2) in a solvent, adding an initiator, and heating in an oven to perform the first step of crosslinking to obtain a first step crosslinked anion exchange resin solution; (4) Adding a thiol reagent and a photoinitiator to the first cross-linked anion exchange resin solution prepared in step (3), placing it under UV light for further cross-linking after coating, to obtain a step-by-step cross-linked high-toughness anion exchange membrane.

3. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (1), the biphenyl monomers are m-terphenyl and p-terphenyl, and the molar ratio of m-terphenyl to p-terphenyl is 1: 1-3, the molar ratio of N-methyl-4-piperidone monomer to m-terphenyl or p-terphenyl is 1:0.5-1, the volume ratio of trifluoromethanesulfonic acid to trifluoroacetic acid is 10:1-3, the volume ratio of the solvent to the total volume of trifluoromethanesulfonic acid and trifluoroacetic acid is 1:1.5-2, and the volume ratio of the solvent to the N-methyl-4-piperidone monomer is 4:1-1.

5.

4. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (1), the solvent is one of dichloromethane, chloroform, tetrachloroethane and carbon tetrachloride, and the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution and potassium carbonate solution.

5. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (2), the molar ratio of the polyaryl piperidine polymer, methyl iodide and 4-vinyl benzyl chloride is 1:1:0.15, and the mass ratio of the polyaryl piperidine polymer to the solvent is 1:5-10; and the solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.

6. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (3), the mass ratio of the quaternized polyaryl piperidine type anion exchange resin containing a portion of styrene structure to the initiator is 125:0.6-1; the mass ratio of the quaternized polyaryl piperidine type anion exchange resin containing a portion of styrene structure to the solvent is 1:5-10.

7. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (3), the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, isomethyl azobisisobutyrate, and azobisisopropylimidazoline hydrochloride; the solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone, and N,N-dimethylformamide; the temperature of the first step cross-linking is 80° C. and the time is 1 hour.

8. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (4), the mass ratio of the thiol reagent, the photoinitiator and the first cross-linking solution obtained in step (3) is 2:1:100-350; The conditions for further cross-linking were heating at 40-60°C and UV irradiation for 25 min.

9. The method for preparing a step-by-step cross-linked high-toughness anion exchange membrane according to claim 2, characterized in that: In step (4), the thiol reagent is one or more of 1,10-decanethiol, 1,5-pentanethiol, 1,8-octanedithiol, 1,6-hexanethiol, and 3,6-dioxa-1,8-octanedithiol; the photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone.

10. A step-wise cross-linked high-toughness anion exchange membrane prepared by the preparation method according to any one of claims 1 to 9, wherein the step-wise cross-linked high-toughness anion exchange membrane has a thickness of 30-80 μm.